Human Resource Management in Times of Change Developments and Challenges - Marco HABBABA (Communications of International Proceedings, 2022)
In the working world of the so called Fourth Industrial Revolution the  competitiveness of  companies depends to a high degree on the qualification, innovativeness and loyalty of its employees which makes Human Resource Management (HRM) a key factor for business success. The rapid change of social and economic conditions during the last years, create the need for a new perspective on HRM, which has not yet been scientifically examined to a profound extent. This paper aims at displaying the evolution of Human Resource Management from its early beginnings in the last century to its current state. The significant  impact of present  societal developments on changes in HRM should be identified and critically viewed.To achieve the  aspired aim a review of specialist and technical literature was conducted. The most powerful influences on HRM, that could be worked out, can be summarized as follows: digitalization, including Artificial Intelligence (AI), globalization, observance of diversity and the Covid-19 Pandemic. The results of the transformations on HRM seem ambivalent and cannot yet be finally evaluated. As it refers to a limited literature data base the present study is primarily meant to set an impulse for further scientific investigation. Especially the final impacts of the ongoing pandemic have yet to be awaited.
Keywords: Human Resource Management; Digitalization; Globalization; Pandemic